2015
DOI: 10.1310/hpj5001-034
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Inventory Systems and Barcode Technology: Impact on Pharmacy Technical Accuracy and Error Liability

Abstract: Purpose: To measure the effects associated with sequential implementation of electronic medication storage and inventory systems and product verification devices on pharmacy technical accuracy and rates of potential medication dispensing errors in an academic medical center. Methods: During four 28-day periods of observation, pharmacists recorded all technical errors identified at the final visual check of pharmaceuticals prior to dispensing. Technical filling errors involving deviations from order-specific se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Simoens (2009) identifies a cost-effectiveness model for traceability implementation based on product defects. Oldland et al (2015) highlight the need to intertwine technical and organizational integration in traceability. While these studies confirm the ongoing interest in traceability, they are either more theoretical in nature or focus on only one specific actor or case in the SC.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Simoens (2009) identifies a cost-effectiveness model for traceability implementation based on product defects. Oldland et al (2015) highlight the need to intertwine technical and organizational integration in traceability. While these studies confirm the ongoing interest in traceability, they are either more theoretical in nature or focus on only one specific actor or case in the SC.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the literature on SC traceability, few studies can be identified that focus on the importance of collaboration between different stakeholders at a sector level (Greenberg, 2014; Oldland et al, 2015; Rosca et al, 2022; Rotunno et al, 2014; Simoens, 2009). Most of the studies adopt a qualitative approach to single firms or dyadic relationships, while a broader network perspective is rarely adopted.…”
Section: Introductionmentioning
confidence: 99%
“…On the ADC screen, the doctor's orders would read "2 bottles per day" at the top and "take out 1 bottle" below, which may also cause the nurse to administer the wrong dosage if the top instructions go unnoticed. Oldland et al [19] found that the medication error rate when using the UDD alone was 0.157%. After ADC implementation, the comparative overall incidence of error was 0.135%.…”
Section: Rate Of Medication Errormentioning
confidence: 99%
“…Barcoded scanning and product verification offers a logical and proven means to decrease errors in inventory (Oldland, Golightly, May, Barber, & Stolpman, 2015). A barcoding system requires scanning of the barcode on the item, as well as scanning the barcode associated with the storage location (also called a "license plate").…”
Section: Alternativesmentioning
confidence: 99%